Design of Augmented Reality Spot in Aceh Polytechnic Information Technology Program Based on Android - Mulia Sari, Devi; Safwan; Ramadhani; Ambri (Jurnal Inotera, 2022)
The Information Technology Study Program laboratory, located on the Aceh Polytechnic campus, is a place of practice for Information Technology Study Program students. This laboratory is often also used by guests for training or testing. Therefore, to make it easier for guests to see the details of the room, an Augmented Reality application for the Android-based Information Technology study program was built as a promotional tool and learning media. This application makes it easy for guests to find out the shape of the room, find out the contents of the room and explain videos about the Information Technology study program using a smartphone. Making this application using Blender software is used to create a three-dimensional model of the room, while Unity software is used to create applications.